2014
DOI: 10.1017/s095026881400226x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal trends of bat-borne rabies in Chile

Abstract: In Chile, while dog rabies has decreased markedly over the last 30 years, bat rabies is still reported frequently. In order to shed new light on the spatiotemporal trends of these reports, we analysed active and passive data from years 1985 and 2012, which included 61 076 samples from 289 counties of Chile. We found that from 1994 to 2012, more than 15 000 bat samples were submitted for diagnostics through passive surveillance, 9·5% of which tested positive for rabies. By contrast, the prevalence of infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0
12

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(54 citation statements)
references
References 23 publications
0
41
0
12
Order By: Relevance
“…The authors of that study found that increased BT was independently associated with longer hospital stay (RR 3.2 in patients undergoing > 4 BT) and increased mortality (RR 4.1 if > 4 BT) [20]. Roubinian et al found that after implementation of blood conservation strategies in critical care patients, the incidence of BT decreased significantly but mortality did not change [21].…”
Section: Discussionmentioning
confidence: 99%
“…The authors of that study found that increased BT was independently associated with longer hospital stay (RR 3.2 in patients undergoing > 4 BT) and increased mortality (RR 4.1 if > 4 BT) [20]. Roubinian et al found that after implementation of blood conservation strategies in critical care patients, the incidence of BT decreased significantly but mortality did not change [21].…”
Section: Discussionmentioning
confidence: 99%
“…The 50-km spatial resolution of Ecoclimate variables mitigate the high spatial lag of finer-resolution climatic layers [52,53], which can produce flawed estimates due to high spatial autocorrelation from statistical downscaling [32,53]. We argue that during exploratory analyses, coarse-scale variables are useful for identifying plausible constraints for species establishment.…”
Section: Discussionmentioning
confidence: 99%
“…To prevent human rabies and to monitor rabies exposure, Colombian government uses a complexity of the Colombian territory [12]. On the other hand, studies of distribution and spatial analysis of human rabies or rabies exposure in humans in Colombia are few but frequently found about livestock rabies [13,14].…”
Section: Author Summarymentioning
confidence: 99%